Chaplin [videorecording (DVD)] - Downey, Robert, Jr., 1965-; Aykroyd, Dan; Chaplin, Geraldine, 1944-; Hopkins, Anthony, 1937-; Jovovich, Milla; Kline, Kevin; Lane, Diane; Miller, Penelope Ann; Chaplin, Charlie, 1889-1977; Robinson, David, 1930- (Lions Gate Films, 2008)
Chaplin's entire life is covered in the biographical film. From his upbringings in the slums of England to his Honorary Oscar in 1972.